2020
DOI: 10.3390/pharmaceutics12060515
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Dendrimer G2-S16 Inhibits Herpes Simplex Type 2 Infection and Protects Mice Vaginal Microbiome

Abstract: The G2-S16 polyanionic carbosilane dendrimer is a promising microbicide that inhibits HSV-2 infection in vitro and in vivo in mice models. This G2-S16 dendrimer inhibits HSV-2 infection even in the presence of semen. Murine models, such as BALB/c female mice, are generally used to characterize host-pathogen interactions within the vaginal tract. However, the composition of endogenous vaginal flora remains largely undefined with modern microbiome analyses. It is important to note that the G2-S16 dendrimer does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
1
9
0
1
Order By: Relevance
“…All these data demonstrate that the G2-S16 dendrimer is capable of interacting with host cellular receptors implied in the RSV infection. We previously described that G2-S16 dendrimer interacts with cellular HS and HBD in HSV infection [ 34 , 35 , 36 , 37 ]. We also previously described that the G2-S16 dendrimer could interact electrostatically with the viral glycoproteins of the viral surface as well as cellular receptors [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…All these data demonstrate that the G2-S16 dendrimer is capable of interacting with host cellular receptors implied in the RSV infection. We previously described that G2-S16 dendrimer interacts with cellular HS and HBD in HSV infection [ 34 , 35 , 36 , 37 ]. We also previously described that the G2-S16 dendrimer could interact electrostatically with the viral glycoproteins of the viral surface as well as cellular receptors [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our results indicates that G2-S16 dendrimer can act in different stages of HIV-1 infection. The main objective of G2-S16 dendrimer is its use as a microbicide, creating a physical barrier that protects the vaginal mucosa from being disrupted [33,34] and inhibiting several viral infections [35][36][37][38]. Thus, these results exacerbate the applicability of this G2-S16 dendrimer, as it is capable of inhibiting macrophages from spreading to other target cells, minimizing viral charge [39], as well as reducing viral reservoirs and sanctuaries due to the ability of macrophages to deliver viral particles to different anatomic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Date from work developed by Guerrero-Beltrán et al (2020) indicated that G2-S16 polyanionic carbosilane dendrimer presents relevant in vitro and in vivo inhibitory activity against herpes simplex type 2 (HSV-2) infection, with complete inhibition of HSV-2 (>90%). Moreover, the G2-S16 provided protection to mice vaginal microbiome, once the composition of vaginal microbiome was similar to healthy mice.…”
Section: Pharmaceutical Nanotechnologymentioning
confidence: 99%